Identificación de los requisitos funcionales para el adecuado tratamiento de aguas residuales industriales y residuos peligrosos sólidos en la PTAR de la empresa de artes gráficas, en cumplimiento a la legislación colombiana en materia de vertimientos (2023)
Environmental problems in the industrial sector have been a central issue for companies in the last decade, which is why greater attention has been paid given its relevance and impact on public health from different nations, which has caused Colombia to adjust strategies that promote the regulation, applicability and monitoring of current environmental regulations. In the national industrial sector of graphic arts, in this case the company: Gráficas Jaiber SAS, makes use of water resources as an input for the production of its products in its production process, this input is susceptible to contamination by inks, solvents and glues, chemical substances also used in the process; When carrying out activities such as washing rollers and other machine tools, this water goes directly to the sewer of the area where the company is located. Thus, with the regulation of environmental regulations, it is necessary to manage resources and implement action plans to comply with national legislation, which is why industrial wastewater is treated, in order to comply with Decree 631. of 2015, through appropriate methods that mitigate the negative impact that is generated and that directly affects the body of water.